(untitled) (Per Musi, 2022)
This article resulted from a naturalistic investigation, quali-quanti, being a case study, in its multi-case aspect. As an objective, the importance of certain nonverbal communication in violin lessons was identified. The investigation was carried out from the analysis of specialized bibliography, a form of direct observation of the action of a violin teacher, a notebook, and a semi-structured interview he was submitted to. The results were triangulated and analyzed, concluding that certain nonverbal communication, if used consciously, gives the teacher the possibility of transmitting his message in a clear and more competent way, obtaining pedagogical-didactic recognition from students. Thus, the classroom environment is more suitable and conducive to a more effective teaching/learning process.